Molecular factors underlying the deposition of intramuscular fat and collagen in skeletal muscle of nellore and angus cattle - Martins, Taiane S. (2015)
Studies have shown that intramuscular adipogenesis and fibrogenesis may concomitantly occur in skeletal muscle of beef cattle. Thus, we hypothesized that the discrepancy of intramuscular fat content in beef from Nellore and Angus was associated with differences in intramuscular adipogenesis and fibrogenesis during the finishing phase. To test our hypothesis, longissimus muscle samples of Nellore (n = 6; BW = 372.5 ± 37.3 kg) and Angus (n = 6; BW = 382.8 ± 23.9 kg) cattle were collected for analysis of gene and protein expression, and quantification of intramuscular fat and collagen. Least-squares means were estimated for the effect of Breed and differences were considered at P ≤ 0.05. A greater intramuscular fat content was observed in skeletal muscle of Angus compared to Nellore cattle (P≤0.05). No differences were observed for mRNA expression of lipogenic and lipolytic markers ACC, FAS, FABP4, SERBP–1, CPT–2, LPL, and ACOX (P > 0.05) in skeletal muscle of Nellore and Angus cattle. Similarly, no differences were observed in mRNA expression of adipogenic markers Zfp423, PPARγ, and C/EBPα (P>0.05) However, a greater PPARγ protein content was observed in skeletal muscle of Angus compared to Nellore cattle (P≤0.05). A greater abundance of adipo/fibrogenic cells, evaluated by the PDGFRα content, was observed in skeletal muscle of Angus than Nellore cattle (P≤0.05). No differences in fibrogenesis were observed in skeletal muscle of Angus and Nellore cattle, which is in accordance with the lack of differences in intramuscular collagen content in beef from both breeds (P>0.05). These findings demonstrate that difference in intramuscular fat content is associated with a slightly enhanced adipogenesis in skeletal muscle of Angus compared to Nellore cattle, while no difference in fibrogenesis.